Composition of black soldier fly prepupae and systematic approaches for extraction and fractionation of proteins, lipids and chitin. (March 2018) - Caligiani, Augusta; Marseglia, Angela; Leni, Giulia; Baldassarre, Stefania; Maistrello, Lara; Dossena, Arnaldo; Sforza, Stefano
Abstract: Black soldier fly (BSF, Hermetia illucens ) constitutes an economic way to convert residual biomasses into a valuable source of biomolecules, such as proteins, lipids and chitin. The present investigation was undertaken to evaluate the feasibility of applying different extraction protocols, either chemical extractions or enzymatic assisted extraction, to recover pure fat, protein and chitin fractions. First, exact proximate composition, total amino acids, fatty acids profile, and N -acetylglucosamine content of the prepupae samples were determined. BSF prepupae biomass contained, expressed on dry weight, 32% proteins, 37% lipids, 19% minerals, 9% chitin. The lipid fraction was easily recovered by organic solvents, while the most challenging issue was the separation of protein from chitin. The best separation was obtained by alkali extraction of proteins (96% of protein recovered) albeit with loss in their integrity as indicated by the measurement of the degree of hydrolysis with the o-phthaldialdehyde method. To avoid protein damage in alkali media, a stepwise protein extraction adopting milder conditions was also explored based on Osborne fractionation method, allowing the recovery of > 85% of BSF high purity and high quality proteins, and the obtainment of chitin-enriched fraction as well. The possibility of using an enzymatic assisted extraction of proteins was also explored, obtaining a maximum nitrogen solubilisation in the best case (with Bacillus licheniformis protease) of about 60%. In this latter case, the chitin fraction obtained also had a significant residual protein content. Graphical abstract: Highlights: Detailed molecular composition of black soldier fly prepupae determined. Several methods to fractionate lipids, protein and chitin systematically explored. Chemical extraction with alkali gave > 90% protein yield in a damaged form. Osborne fractionation gave almost 90% of protein yield preserving integrity. Protease-assisted extraction gave low yields of lipid and 50–70% protein yield in hydrolysed form.